Comparative Efficacy and Safety of Oral Labetalol and Nifedipine in the Management of Preeclampsia: A Randomized Controlled Trial - Jhaveri, Prarthana; Shah, Dhrumil; Chauhan, Kishor (International Journal of Medical Research, 2024)
Background: Preeclampsia, a major cause of maternal and perinatal morbidity, requires effective antihypertensive therapy to control blood pressure, prolong pregnancy, and reduce complications. Labetalol and Nifedipine are commonly used, but their comparative efficacy and safety remain under evaluation. Objective: To compare the efficacy and safety of oral Labetalol and Nifedipine in managing preeclampsia, focusing on blood pressure control, pregnancy prolongation, prevention of convulsions, and fetomaternal outcomes. Methods: In this prospective, open-label, randomized controlled trial, 136 antenatal women with preeclampsia (blood pressure ≥140/90 mmHg with proteinuria) were randomized to receive Labetalol (100 mg twice daily, n=68) or Nifedipine (10 mg thrice daily, n=68) at Dhiraj General Hospital, India, from January 2020 to July 2021. Doses were titrated to achieve blood pressure ≤140/90 mmHg. Outcomes included blood pressure reduction, time to delivery, maternal side effects, complications, mode of delivery, and neonatal outcomes. Statistical analyses included t-tests, chi-square tests, and Kaplan-Meier survival analysis. Results: Nifedipine achieved greater reductions in systolic (121.3 vs. 126.2 mmHg, p=0.048) and diastolic blood pressure (84.3 vs. 87.4 mmHg, p=0.014) compared to Labetalol, with medium effect sizes (Cohen’s d=0.40-0.50). Nifedipine was associated with higher tachycardia (27.9% vs. 5.9%, p=0.003) and cesarean rates (44.1% vs. 26.5%, p=0.059). No significant differences were observed in pregnancy prolongation, proteinuria, or neonatal outcomes (birth weight, stillbirth, NICU admissions; p>0.05). Conclusion: Nifedipine offers superior blood pressure control but higher tachycardia risk, while Labetalol is safer for patients prone to tachycardia. Both drugs yield comparable fetomaternal outcomes.